Design of slime-mold-inspired multi-layered single-electron circuit. Issue 4 (4th July 2019) - Satomi, Kota; Oya, Takahide
ABSTRACT: We propose a new single-electron circuit (SEC) that mimics the behaviours of slime molds. The SEC has unique properties and many advantages including extremely low power consumption. However, the most appropriate information processing way on the SEC has not been established yet. As one approach to find the suitable way, we focus on a natural phenomenon, specifically, the behaviours of slime molds. These molds can feed efficiently and their behaviours can be regarded as performing information processing. Their information-processing-like behaviours can be divided into three functions. Therefore, if we can express these functions on the circuit, it can mimic the slime mold behaviour, i.e. it can operate as a slime-mold-inspired information-processing circuit. In this study, we designed a slime-mold-inspired SEC that utilised three functions based on three types of behaviours, and attempted to imitate these functions by using a multi-layered structure. Our circuit has four layers; three for mimicking the divided functions and the last for output. We evaluated its operation by Monte Carlo simulation and confirmed its operation was correct. This paper indicates design of a new single-electron circuit (SEC). For the SEC to process information efficiently, we focus on the behaviors of slime molds. It is known that these molds can feed efficiently and their behaviors can be regarded as performing information processing. In this study, we designed a slime-mold-inspired SEC having a multi-layered structure. We evaluated its operation by Monte Carlo simulation and confirmed its operation was correct. Figure shows a sample operation of our circuit. (a) is the input pattern and (b) is the output pattern, respectively. The optimal path was revealed. Graphical Abstract: